Planar Dual-Band Branch-Line Coupler With Large Frequency Ratio - Lei Xia (IEEE, 2020)
This work presents a novel planar branch-line coupler topology developed for dual-band operation using an E-shaped impedance transformer network to supplant the conventional microstrip line. Explicit closed-form design equations for dual-band operation are derived using the ABCD matrices. The studied coupler features a large dual-band frequency ratio with a compact size. A prototype coupler centered at 1 and 8 GHz is first presented and experimentally examined to demonstrate the large frequency ratio. Further, another prototype coupler centered at 2.4 and 5.2 GHz for potential WLAN applications is also developed and experimentally characterized. Measurements and simulations for both prototype couplers show good performance within the studied dual-band frequencies.